In tandem for cohesion? Synergies and conflicts between regional and agricultural policies of the European Union - Riccardo Crescenzi; Fabrizio De Filippis; Fabio Pierangeli (London School of Economics and Political Science (LSE), European Institute, 2011)
The paper sets out to analyze the allocations of financial resources accruing to the European regions from the Regional, Rural Development and Agricultural policies of the European Union in order to assess their territorial coordination and synergies and their degree of compatibility with the "general" objective of territorial cohesion. Regression analysis is used to evaluate the relationship between allocated funds (dependent variable) and factors of territorial disadvantage (explanatory variables) covering the 20-year period 1994-2013 and approximately 90% of total Community expenditure. The analysis reveals that both coordination and compatibility with territorial cohesion of the various areas of Community policy have not always improved in response to major policy reforms. The territorial 'vocation' of overall Community spending is weakly linked to its distribution among different policies, but it crucially depends upon how each policy area defines appropriate allocation mechanisms and interventions, based upon the characteristics of each region and its 'local' needs.
Keywords: C24; O18; R11; R58; 330